2006
DOI: 10.1177/0960327106071977
|View full text |Cite
|
Sign up to set email alerts
|

DEHP, bis(2)-ethylhexyl phthalate, alters gene expression in human cells: possible correlation with initiation of fetal developmental abnormalities

Abstract: Diethylhexylphthalate (DEHP) is a widely distributed phthalate, to which humans are exposed to due to its variety of commercial and manufacturing uses. As a plasticiser, it is found in a wide number of products, and metabolites of DEHP have been detected in urine samples from a high percentage ofthe peoplescreened for phthalates. We utilised DNA microarray analysis to evaluate DEHP for gene expression disrupting activity using the human cell line MCF-7, and found that DEHP significantly dysregulated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 45 publications
(28 reference statements)
1
27
0
Order By: Relevance
“…Several human studies have suggested that DEHP has estrogenic effect (Cobellis et al, 2003;Hokanson et al, 2006). PAEs have a weak estrogenic potency compared with estradiol and other estrogenic substances (Jobling et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several human studies have suggested that DEHP has estrogenic effect (Cobellis et al, 2003;Hokanson et al, 2006). PAEs have a weak estrogenic potency compared with estradiol and other estrogenic substances (Jobling et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Recent literatures have suggested that either PAE or NP promotes adipocyte differentiation and induces obesity in mice (Hao et al, 2012a,b); furthermore, these chemicals may have estrogenic effects (Hokanson et al, 2006;Olsen et al, 2005). Muller et al conducted a toxicokinetics study regarding NP exposure in human.…”
Section: Discussionmentioning
confidence: 99%
“…38 However, recent studies in humans indicate a possible estrogenic effect. 17,19,20 The first study demonstrating a possible estrogenic effect for DEHP was reported by Colon et al 19 in Puerto Rico. They have shown that DEHP levels in 45 girls with premature thelarche were statistically significantly higher compared with the 35 control girls.…”
Section: Figurementioning
confidence: 98%
“…16 Although DEHP is considered to be an estrogen agonist and a testosterone antagonist, its mechanisms of toxicity are still not well understood, but are thought to be a function of the disruption of endocrine-regulated gene expression by interaction with estrogen receptor ␣. 17 Although there are some in vivo studies that show no estrogenic effect, 18 several articles have been recently published in which the authors reported a possible estrogenic effect of DEHP in humans, such as a probable role in premature thelarche, 19 endometriosis, 20 and precocious puberty. 21 As far as we know there is no report in which the authors investigated the relationship between DEHP/MEHP levels and pubertal gynecomastia, which develops as a result of an imbalance between androgenic and estrogenic activity.…”
mentioning
confidence: 99%
“…DEHP also inhibits connexin (gap junction) conduction in cardiomyocytes to produce arrhythmias in vitro [29]. Finally, DEHP has been implicated in neurologic defects in exposed developing fetuses [30]. Using the CTD approach to determine the role DEHP may play in these pathophysiologic events, numerous proteins had projected interactions with DEHP, including gamma-amino butyric acid (GABA) A receptors.…”
Section: Computational Systems Biologymentioning
confidence: 99%